7-2x+6=4x-5

Simple and best practice solution for 7-2x+6=4x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-2x+6=4x-5 equation:


Simplifying
7 + -2x + 6 = 4x + -5

Reorder the terms:
7 + 6 + -2x = 4x + -5

Combine like terms: 7 + 6 = 13
13 + -2x = 4x + -5

Reorder the terms:
13 + -2x = -5 + 4x

Solving
13 + -2x = -5 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
13 + -2x + -4x = -5 + 4x + -4x

Combine like terms: -2x + -4x = -6x
13 + -6x = -5 + 4x + -4x

Combine like terms: 4x + -4x = 0
13 + -6x = -5 + 0
13 + -6x = -5

Add '-13' to each side of the equation.
13 + -13 + -6x = -5 + -13

Combine like terms: 13 + -13 = 0
0 + -6x = -5 + -13
-6x = -5 + -13

Combine like terms: -5 + -13 = -18
-6x = -18

Divide each side by '-6'.
x = 3

Simplifying
x = 3

See similar equations:

| (4x-2)*(x+2)*0.5= | | 2n-3=5n+12 | | 25+1x=4+8x | | H(0)=x^2-6x+5 | | 5[x-2]=30 | | (4x-2)*(x+2)= | | s+2[s+3]+[4s-5]=148 | | 5x-22=77 | | 2y+2x^2=8x-8 | | y-0=.5(x-0) | | ax+5bx=7a-c+2ax | | 8x-10=85 | | -3=7-y | | 666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666+9d=2.88 | | -2(5y-10)-y=-4(y-3) | | 14-2(x+8)=5x-(3-34) | | 3(x-5x)=60 | | 5a+6-3a=7a-4 | | x-13+83=180 | | (10-2)-2(1+3)=y | | 6(2x-5)-6=12x-36 | | -5m^3(7n^4-2mn^3+6)= | | z(-5-5*-5)=60 | | 5t=24.5 | | y-0=-4(x+5) | | 17x+3=4(4x+5) | | z(-5-5*-5)=45 | | H(8)=456t | | -3x-15=-(3x+15) | | 3*0.8= | | 7(6y-8)=14y | | 5+16f=-9+16 |

Equations solver categories